2021
DOI: 10.3329/bjch.v45i1.55465
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Child Life & Health in Bangladesh

Abstract: not available BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 1-5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The mortality rate of 3.2% seen in our study is lower than earlier studies in Pakistan involving children, which is encouraging [ 3 , 4 ]. This may reflect improved knowledge with treating children with COVID-19, with similar findings in other countries [ 10 , 85 ].…”
Section: Discussionsupporting
confidence: 65%
“…The mortality rate of 3.2% seen in our study is lower than earlier studies in Pakistan involving children, which is encouraging [ 3 , 4 ]. This may reflect improved knowledge with treating children with COVID-19, with similar findings in other countries [ 10 , 85 ].…”
Section: Discussionsupporting
confidence: 65%
“…The calculated incidence rates of COVID-19 among pediatric patients managed at the University of Ghana Medical Centre (UGMC) in 2020 and 2021 were 9.8% (85/869) and 10.4% (116/1119), respectively, with an overall mortality rate of 10.9% (22/201). This mortality rate (10.9%) among pediatric patients diagnosed and admitted for COVID-19 was lower than seen in Bangladesh and Indonesia at the start of the pandemic, at 13.3% and 40%, respectively [41,48]. However, it was higher than a recent study in Bangladesh (1.4%), as well as the rate reported by the Child Rights International in Ghana, which showed that the incidence rate of COVID-19 among the pediatric population was 4.43% of the total population, with only four deaths recorded out of 2180 children with the virus (0.13% of total deaths) by the end of 2020 [20,49].…”
Section: Discussionmentioning
confidence: 69%
“…This economic misery created nutritional defficiency among rural (84%) and municipal (62.4%) students. In their study, Hussain and Mamun (2020) showed that 64% families were in serious food crisis. This findig has also been corroborated by Antara (2021) reaving that 44% students suffered from malnutrition due to financial crisis.…”
Section: Facing Economic and Familial Crisismentioning
confidence: 99%
“…Helping household activities 8 , involving in income generating activities 9 , facing more financial crisis 10 and forced child marriage 11 are elements of the second group. The last group mainly includes restrictions on outside movement 12 and mental illness 13 . All these studies reviewed conducted their studies at macro level and did not take an attempt to make a comparison between rural and municipal areas.…”
Section: Introductionmentioning
confidence: 99%